Non-alcoholic steatohepatitis (NASH) animal model - Abdul Rahim, Roslina; Abdul Ghani, Azril Shahreez; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; A.Talib, Norlelawati (2021)
This is an experimental animal model that mimics human non-alcoholic steatohepatitis (NASH). In this model, we used a 12% cholesterol diet together with a choline mixture to be induced in rats for 16 consecutive weeks. Liver enzymes were increased, indicating liver injury. Liver histology stainings and grading further proven evidence of NASH.